2014
DOI: 10.1177/1098611114535217
|View full text |Cite
|
Sign up to set email alerts
|

Low Self-Control and Police Deviance: Applying Gottfredson and Hirschi’s General Theory to Officer Misconduct

Abstract: Prior research assessing police misconduct has generally focused on prevalence and demographic correlates while neglecting traditional criminological theories. Some recent research has begun to fill the void in this area, but the link between selfcontrol and police misconduct has yet to be explored. The current study utilizes a behavioral measure of self-control to evaluate the extent to which low self-control predicts police misconduct. Data from a sample of 1,935 police officers from the Philadelphia Police … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 74 publications
3
68
0
1
Order By: Relevance
“…We measure the experience level within an officer's misconduct network by creating a continuous measure of the mean years of service with the CPD for all the co‐complainants at the time of the incident. Although some scholars have suggested officers with greater experience may have more to lose from being named in a complaint and may have acquired the necessary experience to diffuse situations from escalating to force (e.g., Brandl et al., ), others have suggested length of service is associated with increased cynicism and misconduct (Chappell & Piquero, ; Donner & Jennings, ). Here, we examine how being named in a complaint with more tenured officers influences the likelihood of being involved in use of force complaints.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We measure the experience level within an officer's misconduct network by creating a continuous measure of the mean years of service with the CPD for all the co‐complainants at the time of the incident. Although some scholars have suggested officers with greater experience may have more to lose from being named in a complaint and may have acquired the necessary experience to diffuse situations from escalating to force (e.g., Brandl et al., ), others have suggested length of service is associated with increased cynicism and misconduct (Chappell & Piquero, ; Donner & Jennings, ). Here, we examine how being named in a complaint with more tenured officers influences the likelihood of being involved in use of force complaints.…”
Section: Methodsmentioning
confidence: 99%
“…Officer tenure and rank have also been found to impact officer attitudes and behaviors that lead to misconduct. High‐complaint officers are significantly more likely to be younger, less experienced, and more likely to receive departmental disciplinary action (Brandl et al., ; Donner & Jennings, ; Greene et al., ). This has been attributed to younger officers’ heightened activity; “younger officers initiate more contact with the public, conduct a higher proportion of preventative patrolling, and record more crime reports,” which leads to a greater probability of receiving complaints (Adams, ; Brandl et al., , p. 523).…”
Section: Background: Apples Barrels and Networkmentioning
confidence: 99%
“…); future contact with the criminal justice system (Malouf et al . ); police deviance (Donner and Jennings ); stalking (Fox, Nobles and Fisher ); crime among homeless youth (Baron ); cyberbullying (Vazsonyi et al . ); parole failure (Langton ); and general delinquency (Gibbs, Giever and Higgins ).…”
Section: Crime and Self‐controlmentioning
confidence: 99%
“…Research in the context of policing has shown that low levels of self-control are associated with police misconduct (Donner & Jennings, 2014). Even for situations, in which the use of force may be legitimate, it has been argued that self-regulation that allows for the use of non-aggressive forms of behavior may prove to be a more effective and less risky option for police officers (Zaiser & Staller, 2015).…”
Section: Introductionmentioning
confidence: 99%